2005
DOI: 10.1128/jb.187.14.5036-5039.2005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of nlmTE , the Locus Encoding the ABC Transport System Required for Export of Nonlantibiotic Mutacins in Streptococcus mutans

Abstract: Streptococcus mutans UA159, the genome sequence reference strain, exhibits nonlantibiotic bacteriocin (mutacin) activity. In this study, we have combined bioinformatic and mutational analyses to identify the ABC transporter designated NlmTE, which is required for mutacin biogenesis in strain UA159 as well as in another mutacin producer, S. mutans N.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
52
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 28 publications
0
52
1
1
Order By: Relevance
“…Mutacin IV is a two-component bacteriocin that is composed of the NlmA and NlmB peptides, which are encoded by two transcriptionally linked genes (50). The dramatic decrease in the level of mutacin IV produced by the liaS mutant could be due to several factors including a reduction in the transcription of nlmA and nlmB or a deficiency in the export of the NlmA and NlmB peptides by the ABC transporter encoded by nlmT (17); therefore, the levels of transcription of nlmA and nlmT were measured in strains UA159, IBS148, and IBS148/pIB55. As shown in Fig.…”
Section: Vol 76 2008 Lias and Virulence In S Mutans 3095mentioning
confidence: 99%
See 1 more Smart Citation
“…Mutacin IV is a two-component bacteriocin that is composed of the NlmA and NlmB peptides, which are encoded by two transcriptionally linked genes (50). The dramatic decrease in the level of mutacin IV produced by the liaS mutant could be due to several factors including a reduction in the transcription of nlmA and nlmB or a deficiency in the export of the NlmA and NlmB peptides by the ABC transporter encoded by nlmT (17); therefore, the levels of transcription of nlmA and nlmT were measured in strains UA159, IBS148, and IBS148/pIB55. As shown in Fig.…”
Section: Vol 76 2008 Lias and Virulence In S Mutans 3095mentioning
confidence: 99%
“…S. mutans has the capacity to produce mutacin, a bacteriocin, to suppress the growth of other competitor bacteria present in the dental plaque community (12,19,36,38). In particular, S. mutans strain UA159 produces a mutacin that is active against sanguinis group and mitis group streptococci, the main competitors of S. mutans in the oral cavity (17,18,50). It was previously shown that both gbpC expression and mutacin production are modulated by the same regulatory network controlled by LuxS (35).…”
Section: Vol 76 2008 Lias and Virulence In S Mutans 3095mentioning
confidence: 99%
“…Together, the com-controlled NlmC/ImmB (also known as CipB/ CipI) pathway was shown to effect cellular autolysis and extracellular genomic DNA (eDNA) release (37), which contributes to the structural and functional integrity of the S. mutans' biofilm (19,36,37). Involvement of ComDE in regulating the transcription and/or production of mutacins I, IV, V, and VI has also been demonstrated by several labs (12,13,15,19,21,28,37,55,57,58). The antimicrobial spectrum of mutacin IV is specifically against members of the mitis group of oral streptococci, while those of mutacins I, II, and III are broader (38)(39)(40).…”
mentioning
confidence: 99%
“…Based on a survey of 143 strains of S. mutans used to assess bacteriocin production in vitro, 98 strains were reported to produce at least one bacteriocin (44). One of the major pathways of S. mutans for regulating bacteriocin production is via the ComDE two-component signal transduction system (TCSTS) that responds to accumulation of the competence stimulating peptide (CSP) whose precursor peptide is encoded by comC (12,21,28,37,55,58). The ComDE is 1 of 13 TCSTSs in S. mutans (3,24) that help respond to environmental stimuli by transmitting signals from a membrane-bound histidine kinase (HK) to an intracellular response regulator (RR) protein via transphosphorylation, which in turn, regulates the transcription of its target genes (49).…”
mentioning
confidence: 99%
“…However, inhibitory activity was restored only to the comC mutant (Table 2), implicating the ABC transporter complex ComAB in streptocin export. ComAB secretes mature CSP following cleavage of the precursor peptide ComC at a specific Gly-Gly motif (10), and ComAB-like transporters (e.g., NlmTE in Streptococcus mutans [4]) are common exit portals for nonmodified (i.e., class II) Gly-Gly-containing peptide bacteriocins (3,5). Furthermore, a BLAST (1) search of the S. gordonii Challis genome sequence did not reveal an alternative ABC transport system.…”
mentioning
confidence: 99%